ADMINISTRATIVE PROBLEMS ASSOCIATED WITH RISING NEED FOR NEW ADMINISTRTAIVE UNITS IN PAKISTAN - Nawaz, Dawood; Batool, Sarfraz; Fatima, Ishrat (The journal of contemporary issues in business and government, 2021)
Pakistan is suffering from administrative problems since long time and there are many challenges being face in the public institutions. Keeping in view the administrative issues and prevalent bad governance, Pakistan needs to rationalise its administrative structure.There are various aspects of this, including restructuring the whole administrative system which is currently based generally on the federal-provincial-district divisions; introducing extensive and across the board civil-services reforms; revisitingexisting policies and plugging policy gaps.This study has employed analytical and descriptive research methodology to analyze the administrativechallenges and problems in Pakistan by using the two main secondary sources; research articles and books.The main objective of this study was to highlighted the administrative problems and challenges which are being faced inPakistan. In short,to achieve economic growth and to improve the quality of life of the people,Pakistan and its constituent provinces must bring about a radical change in the way in which they are governed and managed, particularly with reference to macroeconomic management, proper policy making, political stability, public administration, good governance, and adequacy of institutional capacity.However, some solutions and recommendations are provided to overcome these administrative problems and challenges.